Distomolars - Exploring the known entity - Dinesh Chand Patidar; Deepika Patidar (Wolters Kluwer Medknow Publications, 2020)
A supernumerary tooth is one that is additional to the normal series and can be found in any region of the dental arch. A distomolar, also called as "fourth molars," is a supernumerary tooth that is positioned distal to third molars. Distomolar can be found completely erupted in the dental arch, or it could be partially or entirely impacted. This literature review attempts to highlight the prevalence, etiology, morphology, complications, and diagnosis of distomolars. Various literatures reveal that supernumerary teeth are more frequently seen in the maxilla with a male predilection and their prevalence in the permanent dentition has been approximated to range from 0.1% to 3.6%. A distomolar may have a normal morphology or have a much smaller dimension than adjacent third molars. Molariform (tuberculated) shape is most frequently observed by various authors in their studies. Distomolars are usually found impacted within the jaws and may lead to several complications. Even though the frequency of distomolars is low, dental surgeons should always be aware of the presence of distomolars during radiographic or clinical examinations. A thorough knowledge and information about this supernumerary entity may definitely provide a hope for an early detection and appropriated treatment planning so as to prevent or minimize any complications created by them.